MONITORING THE MEDIA PH VALUE IN THE MIXTURE OF JUICE OF CITRUS AURANTIUM IN SYNTHETICALLY PREPARED GASTRIC JUICE: AN EXPERIMENTAL STUDY - Buddhika, *Nuwansiri Liyanage Shalimal; Sadini Rukshala, Abeysooriya; J.M.P.R.K, Jayasinghe (International Journal of Ayurveda and Pharma Research, 2016)
According to Sri Lankan Ayurveda pharmacopeia, indication of Juice of Abuldodam (Citrus aurantium) in afternoon or evening is a good treatment for Amla pitta. According to Ayurveda Citrus aurantium is sour (Amla rasa) in taste, Amlavipaka, Guru Guna and Ushnaveerya. It is Kapha-Vathashamaka, Rochana, Deepana and Anulomana in Anna Pachanavyuha (GIT). Citric acid, pectin, lemon oil and carotene etc. are the main chemical compounds of Citrus aurantium. Common attitude is that most probably acidic fruits may be a cause for increasing the acid condition in the stomach. Society disagrees to use the juice of Citrus aurantium as a treatment of Amlapitta. But some Ayurveda and Traditional physicians have been used the juice of Citrus aurantium in the management of Amlapitta. Gastric acid is the digestive fluid, formed in the which shows of 1.5 to 3.5 and is composed of (HCl) (around 0.5%, or 5000 ppm). Gastric juice is a strong acid (as high as 0.1 M) usually secreted by the glands in the lining of the stomach and usually essential for the digestion. The amount of gastric juice in the stomach will vary from person to person. In the study, gastric juice was prepared in synthetically at the level of normal pH value in stomach following standard procedure. 10 samples of gastric juice were arranged in various pH values (0.86-13.11). 25ml of juice of Citrus aurantium was mixed into each sample. The pH value was measured with the temperature in three durations, on time, after 5 minutes and after 10 minutes. The P values were measured with standard software. The founded P valve is 0.955 at 95% confidence level. It can be concluded that there is no significant variation of the media pH value in the mixture of Juice of Citrus aurantium in synthetically prepared gastric juice.